(untitled) (International Journal of Engineering and Computer Science, 2022)
This paper focuses on improved physical modeling techniques for small scale reinforced concrete structured subjected to moment represents.Abeam is a component which resist moment that come to the beam directly for any kind of distributed load or imposed point load. In real life it’s quite impossible to analyze a beam experimentally before starting construction of a particular structure. It will be easier to check by a small-scale model of that prototype model. After getting a relationship between a prototype model and half scale model, it will be. easier to analyze real life beam model’s moment taking capacity only by testing a half scale. model.Assuming a real-life beam model having a length = 10 ft (Simply supported beam) Beam section 12"X14" where width = 12 inch and depth = 14 inch. Support reactions at point A and point B is equal to P/2 kip. For imposed load P kip, maximum bending moment = 2.5P kip-ft. For different values of P, maximum bending moment is different for this particular beam. If P = 10kip, then maximum moment =2.5*10 = 25kip-ft = 300 kip -in Steel ratio: Considering compressive strength of concrete, fc’ = 3.5 ksi and Tensile strength of steel, fy = 60ksi. Evaluation of the potential of a real-life beam model at the moment and its half scale model. Another aim is to figure out a relationship between a real-life beam models moment carrying capacity and a half scale model such that it can be conveniently sorted the moment carrying capacity of a real-life beam model by checking the half scale model